Perisa koko - Omar, Muhammad Nor; Faridah, A. A (Malaysian Agricultural Research and Development Institute, 1987)
A brief description of cocoa flavour including the isolation and the determination of its aroma compounds are discussed. Pyrazines and carbonyls are the two important compounds contributing to the cocoa flavour. These compounds are influenced by factors such as geographic location, varieties, fermentation and roasting. Other non-volatile compounds such as theobromine and polyphenol also contribute to the bitter and astringent flavour of cocoa products.